2005
DOI: 10.1111/j.1532-7795.2005.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Dieting, Romance, and Sexual Activity in Adolescent Girls: Relationships Over Time

Abstract: Romantic relationships constitute an important, but understudied, developmental context for accommodation to pubertal change. Using a nationally representative sample of 5,487 black, white, and Hispanic adolescent females, this study examined associations among body mass index, current romantic involvement, and dieting. For each one point increase in body mass-index (BMI), the probability of having a romantic relationship decreased by 6%. Further, involvement in a nonsexual romantic relationshipbut not involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 40 publications
5
60
2
1
Order By: Relevance
“…In contrast, two more-recent studies have found evidence of a link between body weight and sexual behavior. Using data from Add Health on females ages 12-17, Halpern et al (2005) found that a higher BMI was associated with a lower probability of being in a sexual relationship. Cawley et al (2006) used data from the 1997 National Longitudinal Survey of Youth (NLSY) as well as data from the Add Health.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast, two more-recent studies have found evidence of a link between body weight and sexual behavior. Using data from Add Health on females ages 12-17, Halpern et al (2005) found that a higher BMI was associated with a lower probability of being in a sexual relationship. Cawley et al (2006) used data from the 1997 National Longitudinal Survey of Youth (NLSY) as well as data from the Add Health.…”
Section: Introductionmentioning
confidence: 97%
“…Neither Cawley et al (2006) nor Halpern et al (2005) treated adolescent body weight as endogenously determined. Therefore, the negative relationship between bodyweight and sexual behavior documented by these authors could be due to the influence of unobservables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the longitudinal study conducted by Halpern, King, Oslak, & Udry (2005) with seventh and eight grade girls established that girls with higher levels of body fat were less likely to report dating activity over the past 6 months.…”
Section: Romantic Relationshipsmentioning
confidence: 99%
“…From a fat studies perspective this is crucial to understanding fat people's sex lives, yet it is only considered in a minority of the sample articles and even then in rather limited ways (Bajos, 2010;Chen and Brown, 2005;Halpern, 2005;Swami and Tovée, 2009). …”
Section: Critiquing Failurementioning
confidence: 99%